2009
DOI: 10.1073/pnas.0901591106
|View full text |Cite
|
Sign up to set email alerts
|

An integrated genome screen identifies the Wnt signaling pathway as a major target of WT1

Abstract: WT1, a critical regulator of kidney development, is a tumor suppressor for nephroblastoma but in some contexts functions as an oncogene. A limited number of direct transcriptional targets of WT1 have been identified to explain its complex roles in tumorigenesis and organogenesis. In this study we performed genome-wide screening for direct WT1 targets, using a combination of ChIP-ChIP and expression arrays. Promoter regions bound by WT1 were highly G-rich and resembled the sites for a number of other widely exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 44 publications
4
60
0
1
Order By: Relevance
“…Of interest, loss of WT1, in turn, is able to amplify b-catenin signaling, because WT1 is a negative inhibitor of Wnt/b-catenin signaling. 40,41 Therefore, b-catenin activation and loss of WT1 effectively form a feed-forward vicious cycle, leading to exaggerated podocyte injury ( Figure 5I). …”
Section: Discussionmentioning
confidence: 99%
“…Of interest, loss of WT1, in turn, is able to amplify b-catenin signaling, because WT1 is a negative inhibitor of Wnt/b-catenin signaling. 40,41 Therefore, b-catenin activation and loss of WT1 effectively form a feed-forward vicious cycle, leading to exaggerated podocyte injury ( Figure 5I). …”
Section: Discussionmentioning
confidence: 99%
“…Since the crystal structure of the KLF4 protein has not yet been determined, it is not clear if KLF4 interfaces with ␤-catenin in a similar manner. Recently, it was reported that WT1, another C 2 H 2 zinc finger protein, competes with TCF4 for CBP binding and thus inhibits Wnt signaling (23). Since KLF4 also binds p300/CBP (9), KLF4 may compete with ␤-catenin/TCF4 for p300/CBP binding as well.…”
Section: Discussionmentioning
confidence: 99%
“…b-catenin/Wnt signaling, which represents a pivotal step driving PEC differentiation into podocytes during kidney development [7]. Indeed, conditional b-catenin-knockout mice in which Ctnnb1 (mouse b-catenin gene) was removed during later stages of nephrogenesis in PECs show underdeveloped glomerular capillary tufts, with podocytes replacing normal flat PECs.…”
Section: Role In Normal Glomerular Developmentmentioning
confidence: 99%